2010
DOI: 10.1093/jac/dkq192
|View full text |Cite
|
Sign up to set email alerts
|

Tn1546 structures and multilocus sequence typing of vanA-containing enterococci of animal, human and food origin

Abstract: A moderate variability in Tn1546 structure has been detected among unrelated vanA-containing enterococci of different origins, showing three new structures including two new ISs. A high diversity of STs was detected among E. faecium strains, especially among non-clinical strains, and new STs have been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 12 publications
2
24
0
1
Order By: Relevance
“…Moreover, this gene is usually located in transposon Tn1546 which facilities its mobilization and transference to other microorganisms. Our isolate showed identical Tn1546 structure to one previously described in two studies carried out in Spain, one of them in an E. faecium isolate from a wild black rat [13] and the other one in a clinical isolate [19]. This transposon and other resistance genes are often mobilized by the same plasmid, being transferred at the same time when one of the antimicrobial agents is used.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, this gene is usually located in transposon Tn1546 which facilities its mobilization and transference to other microorganisms. Our isolate showed identical Tn1546 structure to one previously described in two studies carried out in Spain, one of them in an E. faecium isolate from a wild black rat [13] and the other one in a clinical isolate [19]. This transposon and other resistance genes are often mobilized by the same plasmid, being transferred at the same time when one of the antimicrobial agents is used.…”
Section: Discussionsupporting
confidence: 67%
“…The structure of the transposon Tn1546, in the case of vanA isolates, was determined thanks to the use of specific primers and the sequencing of the obtained amplicons (Table 1) [19]. …”
Section: Vancomycin Resistance Mechanismsmentioning
confidence: 99%
“…This gene could have a great role in the exchanging genetic mobile elements and could also be implicated in the adaptation of these bacteria to the hospital environment [29,30].Remarkably, our vanA E. faecium isolates presented a multiresistance phenotype, being resistant, in addition to glycopeptides, to erythromycin, tetracycline, ciprofloxacin, ampicillin, kanamycin, streptomycin, pristinamycin, and trimethoprimsulfamethoxazole. In the case of resistance genes erm(B) and tet(M), it is interesting to mention that they have been previously detected in the same conjugative plasmid as the van(A) gene, which indicates that coselection processes might have happened [31]. Our VRE strains were still susceptible to high dose of gentamicin, similar to what was found in a previous study reported in Tunisia showing the emergence of epidemic CC17 clones of vanA E. faecium that were also sensitive to high dose of gentamicin [6].…”
Section: Discussionmentioning
confidence: 99%
“…Presence of a transposase (IS204/IS1001/IS1096/IS1165) between vanY and vanX was partially resolved. This vanA cluster constitutes a subtype of Tn1546-like elements which often bear IS elements like ISEf1, IS1678, or IS1216 V, ISEfa5, IS19-like between vanX and vanY (Werner et al, 2008;Jung et al, 2007;Camargo et al, 2005;Lopez et al, 2010). ermB, which encodes resistance to macrolides, lincosamides, and streptogramin B antibiotics was also identified on pLG1.…”
Section: Resistancementioning
confidence: 99%